Sleep quality moderated the mediating effect of BMI and waist circumference on the relationship between screen time and mental health in Chinese adolescents - Wang, Yi; Wu, Huipan; Wu, Jian; Ma, Yuanyuan; Wang, Jinxian (Frontiers in Pediatrics, 2025)
ObjectiveThis study aimed to investigate whether body mass index and waist circumference can moderate the relationship between screen time and adolescent mental health, and whether sleep quality can moderate these effects.MethodUsing a stratified cluster random sampling method, 5,713 adolescents aged 13–18 years were selected from six administrative regions in China for a questionnaire survey. Data analysis used statistical methods such as Pearson correlation analysis. The mediation model was tested using the PROCESS (version 3.3) SPSS macro model 4 developed by Hayes, and model 7 was used to test the moderation model.ResultsScreen time was negatively correlated with adolescent mental health (r = −0.10, p < 0.001) and positively correlated with BMI (r = 0.03, p < 0.05). Screen time has a significant negative effect on adolescents’ mental health [β = −0.20, SE = 0.07, p < 0.01, 95% CI = (−0.34, −0.06)], while BMI mediates the relationship between screen time and mental health [β = −0.89, SE = 0.12, p < 0.001, 95% CI = (−1.11, −0.66)]. Additionally, sleep quality moderates the relationship between screen time and mental health in adolescents [β = 0.04, SE = 0.01, p < 0.001, 95% CI = (0.02, 0.07)]. There was no correlation between screen time and waist circumference (r = −0.005, p > 0.05), but there was a negative correlation between waist circumference and mental health (r = −0.04, p < 0.01). Waist circumference did not mediate the relationship between screen time and mental health (p > 0.05), nor did sleep quality moderate the relationship between screen time and waist circumference (p > 0.05).ConclusionBMI plays a partial mediating role between screen time and mental health among Chinese adolescents. Additionally, sleep quality weakens the association between screen time and mental health. Therefore, it is recommended to alleviate mental health issues caused by excessive screen time among adolescents by promoting sleep quality.